Answer:
u = log 22 / log 6
u = 1.725
Step-by-step explanation:
Let's start by saying:
When ever you have an exponential equation with a different base, you attack
Answer:
lg22/lg6
Step-by-step explanation:
6^u = 22
lg(6^u) = lg22
ulg6 = lg22
u = lg22/lg6
Answer: 11.9%
Step-by-step explanation:
Answer:
f⁻¹(x) = (8-x)/3 and it is a Function.
Step-by-step explanation:
Given is f(x) = -3x+8
Suppose y = f(x), then y = -3x + 8
Solving for x:-
-3x + 8 = y
-3x = y - 8
3x = 8 - y
x = (8-y)/3
Now interchanging x and y:-
y = (8-x)/3
Here, y is inverse function i.e. f⁻¹(x)
Hence, f⁻¹(x) = (8-x)/3
Since f⁻¹(x) is a linear expression of x, therefore it is a function.
B. no endpoints.
C. two endpoints.
D. an undefined length.
Answer:
the sign of the product would be a negative or "-"
Step-by-step explanation:
The sign of the product of -2/9 × 1/7 is negative because one of the numbers being multiplied is negative and the other is positive.
In mathematics, the sign of a product is determined by the sign of the numbers that are being multiplied. When multiplying two numbers, if both numbers are positive or both numbers are negative, the product will be a positive number. If one number is positive and one is negative, the product will be a negative number.
In our case, we are multiplying -2/9 and 1/7. The number -2/9 is negative and the number 1/7 is positive. Since one number is positive and the other one is negative, the sign of the product -2/9×1/7 will be negative. Thus, we enter '-' for negative.
#SPJ2
y = -3x +5
y = 2x
y = 3x + 5
The correct equation for y in terms of x would be, y = - 3x + 5
Hence, option 2 is true.
Used the concept of an equation that states that,
An equation is a group of numerical variables and functions that have been combined using operations like addition, subtraction, multiplication, and division.
Given that the expression is,
6x + 2y = 10
Now, simplify the equation for y in terms of x as,
6x + 2y = 10
Subtract both sides by 6x,
2y = - 6x + 10
Divide both sides by 2,
y = - 3x + 5
So, The correct equation would be, y = - 3x + 5
Thus, option 2 is true.
To learn more about the equation visit:
#SPJ6
Answer:
y = - 3x + 5
Step-by-step explanation:
Given
6x + 2y = 10 ( subtract 6x from both sides )
2y = - 6x + 10 ( divide all terms by 2 )
y = - 3x + 5
$5,375 x 12 = $64,500 x 2 = $129,000
Answer:
just use this formula and plug in your numbers from the question.
Maximum Loan for a house= $129,000
monthly pay * 12. So $5,375*12=$64,000.
$64,000*2=$129,000.
Maximum spent on a House=$144,000
$129,000+ $15,000= $144,000
Step-by-step explanation:
Rule from the lesson:
Maximum loan for a House = 2(Annual Gross pay) , that is 2*your annual gross pay.
Maximum spent on a House= Maximum Loan + Down Payment